The Ideal Image of Girls in The Fashion Rubric of Gadis 2020 Annual Edition - Sonia Indra Leitte Paula (Kata Kita: Journal of Language, Literature, and Teaching, 2021)
Gadis is the oldest girl’s magazine in Indonesia. In 2020, Gadis published its annual edition with its trademark theme that is Fashion and Beauty. As part of the media, Gadis must select certain pictures to be published in the magazine, thus the pictures are the ideal portrayal of girls. I used Semiotics theory by Roland Barthes to know the girls’ ideal image and how Gadis constructed it. I found out that confidence, friendliness, and playfulness are three ideal images in the fashion rubric of Gadis 2020 Annual Edition. The finding of my analysis is that: girls’ ideal image that Gadis represents is influenced by the characteristics of generation Z who are the target market of Gadis, as well as Indonesian culture that is being friendly. Keywords: Girls’ magazine, Gadis magazine, Ideal Image, Semiotics